Analisis Program Goes to Campus dengan Goal Oriented Evaluation Model (GOEM) dalam Menumbuhkan Minat Siswa Kelas 11 SMA Al Basyariah - Hesti Kusumangingrum; Cinta Pradana Putri; Aziza Sulistyawati; Bevan Multazam Pramudito; Davin Rofiul Hidayah; Maura Karisma Tiar (Pusat Riset dan Inovasi Nasional, 2025)
The Goes to Campus program is a program that provides insight into various aspects of campus life, such as available study programs, academic environment, career prospects, and direct experience of the lecture atmosphere to students. The purpose of the evaluator's role is to transmit the Goes to Campus program to the effectiveness of school programs using the Goal Oriented Evaluation Model (GOEM), which focuses on achieving program objectives. The results of the study indicate that this program is relevant and has a positive impact on students' understanding of the world of lectures. The implication of this study is the need to develop similar programs with adjustments to student needs and the implementation of more mature strategies.